2017
DOI: 10.1186/s12940-017-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Food-borne disease and climate change in the United Kingdom

Abstract: This review examined the likely impact of climate change upon food-borne disease in the UK using Campylobacter and Salmonella as example organisms. Campylobacter is an important food-borne disease and an increasing public health threat. There is a reasonable evidence base that the environment and weather play a role in its transmission to humans. However, uncertainty as to the precise mechanisms through which weather affects disease, make it difficult to assess the likely impact of climate change. There are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 42 publications
(47 reference statements)
1
23
0
3
Order By: Relevance
“…Similarly, a time-series analysis showed that rates of enteric illness varied seasonally within Canada, with a strong association between infections with Campylobacter spp., pathogenic Escherichia coli and Salmonella spp., and ambient air temperature (24). These results are generally similar to those reported from other countries (13)(14)(15)(16)(17)25,26).…”
Section: Effect Of Climate Change On Foodborne Illnesssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, a time-series analysis showed that rates of enteric illness varied seasonally within Canada, with a strong association between infections with Campylobacter spp., pathogenic Escherichia coli and Salmonella spp., and ambient air temperature (24). These results are generally similar to those reported from other countries (13)(14)(15)(16)(17)25,26).…”
Section: Effect Of Climate Change On Foodborne Illnesssupporting
confidence: 89%
“…Food safety, food security and food system challenges are thought to represent the most significant climate change-related threats to human health globally (7)(8)(9)(10)(11)(12). Researchers anticipated a link between foodborne illness and climate change, since the pathogens that cause many foodborne infectious diseases are known to be influenced by climate and weather variables (13)(14)(15)(16)(17)(18)(19)(20)(21). Despite their obvious importance, these food safety issues have received little attention in the climate-health literature relative to other health indicators (12).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the controversy surrounding climate change, evidence suggesting that climatic conditions affect the level of pathogens in seafood (Marques et al., 2010; Smith et al., 2015) and that they are correlated with the occurrence of foodborne illnesses is available (Aik et al., 2018; Choi et al., 2015; Jiang et al., 2015; Lake, 2017; Park, Park, & Bahk, 2018). The World Health Organization recently suggested that its member nations should increase awareness of the increase in foodborne diseases associated with climate change and urged relevant authorities and stakeholders to incorporate food safety measures for mitigating the effect of climate change on health (WHO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On estime que les défis liés à la salubrité des aliments, à la sécurité alimentaire et au système alimentaire posent les plus grandes menaces à l'échelle mondiale pour la santé humaine, du fait de leur lien avec les changements climatiques (7)(8)(9)(10)(11)(12). Les chercheurs s'attendaient à un lien entre les maladies d'origine alimentaire et les changements climatiques en raison de la sensibilité aux variables climatiques et météorologiques des agents pathogènes responsables de nombreuses maladies d'origine alimentaire (13)(14)(15)(16)(17)(18)(19)(20)(21). Malgré leur importance évidente, les questions relatives à la salubrité des aliments ont reçu peu d'attention dans les articles sur le lien entre le climat et la santé, comparativement à d'autres indicateurs de la santé (12).…”
Section: Introductionunclassified